The Concomitant Evolution of Wear and Squeaking in Dual-Severity, Lubricated Wear Testing of Ceramic-on-Ceramic Hip Prostheses - Sanders, Anthony (2012)
Ceramic-on-ceramic hip bearings were tested in short-term wear tests with a systematically varied contact force. Continuous vibration and intermittent surface roughness measurements were obtained to elucidate potential causes of in vivo hip joint squeaking. The three-phase test comprised alternating cycles of edge loading and concentric articulation, always using ample serum lubricant. A 50,000-cycle wear trial in which the contact force during concentric articulation was distant from the head’s wear patch yielded no squeaking and practically no liner roughening. In 10-cycle trials of an edge-worn head coupled with a pristine liner, the contact force was varied in magnitude and point of application; immediate, recurrent squeaking occurred only when the contact force exceeded a critical threshold value and was centered upon the head’s wear patch. In a 27,000-cycle wear trial with the contact force applied near the margin of the head’s wear patch, recurrent squeaking emerged progressively as the liner’s inner surface was roughened via its articulation with the worn portion of the head. The results reveal key conditions that yield recurrent squeaking in vitro in various scenarios without resorting to implausible dry conditions. A fundamental theory explains that hip squeaking is induced by myriad stress waves emanating from asperity collisions; yet, the root cause is edge loading.